2007
DOI: 10.1021/om700797k
|View full text |Cite
|
Sign up to set email alerts
|

Pd(0)-Catalyzed Phosphorus−Carbon Bond Formation. Mechanistic and Synthetic Studies on the Role of the Palladium Sources and Anionic Additives

Abstract: Pd(PPh 3 ) 4 , Pd(dba) 2 , Pd(OAc) 2 , and PdCl 2 , have been evaluated as possible Pd(0) sources for the palladium-catalyzed P-C bond formation via a cross-coupling of aryl halides with H-phosphonate diesters. It was found that the most efficient catalytic system can be generated from Pd(OAc) 2 with a key role being played by Pd(II) and Pd(0) species with coordinated acetate ions. The reactivity of differently ligated Pd(II) complexes was determined, and 31 P NMR spectroscopy studies were carried out to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
81
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 36 publications
2
81
0
1
Order By: Relevance
“…As far as the palladium source is concerned, it was found that in contrast to PdA C H T U N G T R E N N U N G (PPh 3 ) 4 used in Hiraos original procedure, [1] catalytic systems generated in situ from PdA C H T U N G T R E N N U N G (OAc) 2 and appropriate phosphine ligands, were usually superior in terms of reactivity for promoting the C À P bond formation. [9,11,[20][21][22]24,27] All these improvements, for which a mechanistic basis has been provided in recent years, [19,27,28,[29][30][31] lend themselves into a modified catalytic cycle for the palladium-mediated formation of the C À P bond as shown in Scheme 2. Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…As far as the palladium source is concerned, it was found that in contrast to PdA C H T U N G T R E N N U N G (PPh 3 ) 4 used in Hiraos original procedure, [1] catalytic systems generated in situ from PdA C H T U N G T R E N N U N G (OAc) 2 and appropriate phosphine ligands, were usually superior in terms of reactivity for promoting the C À P bond formation. [9,11,[20][21][22]24,27] All these improvements, for which a mechanistic basis has been provided in recent years, [19,27,28,[29][30][31] lend themselves into a modified catalytic cycle for the palladium-mediated formation of the C À P bond as shown in Scheme 2. Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…First, we performed the reactions of 9a (1.2 eq) with a variety of antimony reagents (1a-6) to compare the reactivity using 5 mol% of Pd(PPh 3 ) 4 as catalyst in 1,4-dioxane at 60°C under argon atmosphere (entries [1][2][3][4][5][6][7][8]. In comparison with these results, triphenylantimony dicarboxylates (1a, 2) and pentavalent bismuth(V) compounds (7,8) afforded the expected diethyl phenylphosphonate (10) in good to high yields along with homo-coupling product (11) and reductive products (12,13). Among these, triphenylantimony diacetate (1a) appeared to be the best substrate for this reaction in terms of the yield (77%) of the cross-coupling product (10) and reaction time (6 h).…”
Section: Resultsmentioning
confidence: 94%
“…We also examined a similar reaction using other catalytic systems such as Pd(dba) 2 , Pd(dba) 2 -dppf, PdCl 2 , Pd(OAc) 2 , and PdCl 2 (PPh 3 ) 2 . They were inferior to Pd(PPh 3 ) 4 in the terms of the reaction time and yield of the cross-coupling product (entries [12][13][14][15][16]. The screening of solvent showed that the reaction proceeded effectively in dioxane (94%), 1,2-dichloroethane (DCE) (78%), 1,2-dimethoxyethane (DME) (75%) and tetrahydrofuran (THF) (71%) whereas toluene, CH 3 CN, N-methylpyrrolidone (NMP) and EtOH gave inferior results (entries [17][18][19][20][21][22][23].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations